2019
DOI: 10.1177/0022002719863844
|View full text |Cite
|
Sign up to set email alerts
|

Rebel Territorial Control and Civilian Collective Action in Civil War: Evidence from the Communist Insurgency in the Philippines

Abstract: Under what conditions do rebel organizations control territory during civil war? How do civilians influence the distribution of territorial control? This article introduces a civilian agency theory, emphasizing community collective action capacity (CAC) defined by underlying social network structure, to complement existing explanations of territorial control. I argue communities with greater CAC mobilize information and resources more efficiently, increasing belligerents’ incentives to control territory. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 74 publications
0
43
0
Order By: Relevance
“…One of the main reasons rebels seek to control territory is to gain access to population-based resources (Rubin 2020), which include civilians' provision of food, financial contributions, shelter, and perhaps most importantly, information. 4 Rebels can access these population-based resources through violent coercion, but they can also use institutions, which reduce the need to rely on coercion to control the civilian population, which is not costless for rebel groups.…”
Section: What Rebels Wantmentioning
confidence: 99%
“…One of the main reasons rebels seek to control territory is to gain access to population-based resources (Rubin 2020), which include civilians' provision of food, financial contributions, shelter, and perhaps most importantly, information. 4 Rebels can access these population-based resources through violent coercion, but they can also use institutions, which reduce the need to rely on coercion to control the civilian population, which is not costless for rebel groups.…”
Section: What Rebels Wantmentioning
confidence: 99%
“…In areas in which belligerent forces are more reliant on local collaboration, the civilian population may leverage its (limited) power to shape the local political order under belligerent presence (Arjona 2016;Kaplan 2017;Rubin 2020). Even where communities lack capacity to influence belligerent behavior, civilians may (rationally) choose to remain in their homes despite violence (Engel and Ibáñez 2007;Melander and Öberg 2006;Steele 2009).…”
Section: Contributions To Existing Literaturementioning
confidence: 99%
“…;Jackson, Rodriguez-Barraquer, and Tan 2012;Siegel 2009), including in conflict settings(Arjona 2016;Dorff 2017;Gade 2020;Kaplan 2017;Krause 2018;Parkinson 2013;Petersen 2001;Rubin 2020) Kaplan (2017). argues that communities with greater "organizational capacity" are more successful in retaining autonomy from belligerent control and escaping violence during civil war and, though left unexplored suggests that organizational capacity may facilitate collective exodus from conflict zones (pg.…”
mentioning
confidence: 99%
“…Although recent studies have explored the conditions under which these types of community level responses to violent actors are more likely to emerge, and their potential effects on armed groups' behavior (Arjona, 2016;Kaplan, 2017;Masullo, 2017;Rubin, 2019), we still know little about why they take different forms when they emerge. Grassroots responses range from everyday forms of resistance (Scott, 1985) and disguised collective action (Fu, 2017) to the creation of zones of peace (Hancock & Mitchell, 2007) and the formation of community-initiated militias (Jentzsch, 2014;Schubiger, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This omission is problematic: not only is noncooperation common enough to be important in its own right, but it also has the power to shape war trajectories and outcomes in consequential ways. Recent studies have shown that it can affect the level of violence that armed groups inflict on civilians (Kaplan, 2017), the distribution of territorial control and the establishment of rebel governance (Arjona, 2016;Rubin, 2019), communities' resilience to communal violence (Krause, 2018), and communities' capacity to engage in postconflict reconstruction (Masullo, 2018).…”
Section: Introductionmentioning
confidence: 99%